2019
DOI: 10.1038/s41598-019-38941-9
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of deuterium irradiation on graphite boronized in the NSTX-U tokamak

Abstract: Boronization has been used in the National Spherical Torus-Upgrade (NSTX-U) as first wall conditioning technique. The technique decreased the oxygen impurities in the plasma and the O% on the Plasma Facing Components (PFC) as measured with an in-vacuo probe. Samples were extracted from tiles removed from the tokamak for post-mortem and controlled studies. Ex-vessel low energy and fluence D 2 + and Ar + irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Following the oxidation and its associated D retention, the retained D is removed when the oxides are removed from the surface by the Ar irradiations that followed the D implantation, and this can be seen as the signals associated with the main deuterium desorption channels 30 are directly responsive to the ion flux, i.e., D 2 O and D 2 . 28 The experimental observations show qualitative agreement with the behavior predicted by the simulations. According to the computational results, the BCOD complex is expected to retain nearly 35% of the incident D, and a similar behavior is observed experimentally since the irradiated sample traps deuterium during the first two irradiations Multiple experiments have been conducted to study D retention on the Li-C-O system and can be found in Refs.…”
Section: A Boronized or Lithiated Carbon Surfacesupporting
confidence: 75%
See 1 more Smart Citation
“…Following the oxidation and its associated D retention, the retained D is removed when the oxides are removed from the surface by the Ar irradiations that followed the D implantation, and this can be seen as the signals associated with the main deuterium desorption channels 30 are directly responsive to the ion flux, i.e., D 2 O and D 2 . 28 The experimental observations show qualitative agreement with the behavior predicted by the simulations. According to the computational results, the BCOD complex is expected to retain nearly 35% of the incident D, and a similar behavior is observed experimentally since the irradiated sample traps deuterium during the first two irradiations Multiple experiments have been conducted to study D retention on the Li-C-O system and can be found in Refs.…”
Section: A Boronized or Lithiated Carbon Surfacesupporting
confidence: 75%
“…These measurements can be used as evidence of retention of D by the BCOD system. In this case, the D irradiations have a twofold effect of the boronized graphite system, i.e., they induce oxidation of the surface (this effect has also been observed in the LiCOD system 10,29 ) and they implant D, which will be retained by the increased O on the surface (since both the D and O concentrations are now increasing on the surface 28 ). The increment in the oxygen concentration can be attributed to two mechanisms.…”
Section: A Boronized or Lithiated Carbon Surfacementioning
confidence: 84%
“…As a result, atomistic simulation methods such as molecular dynamics (MD) have emerged as a critical tool in characterizing PMIs. To this end, a combination of classical molecular dynamics (CMD) and density functional theory (DFT) approaches have been used to investigate reactions between carbon/boron/oxygen mixtures and their irradiation by deuterium [2,[6][7][8]. This has provided valuable insight into species transport, sputtering behavior, and other events that are relevant to PMIs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of boron within oxidized amorphous carbon mixtures has been shown in simulations-and corroborated via experiment-to reduce the amount of sputtered carbon from to deuterium bombardment [2,6,7]. Furthermore, boron has been shown to prevent the sputtering of oxygen within amorphous carbon by deuterium via the formation of oxidized boron states [6][7][8]. The hydrogen uptake of ordered carbon/boron mixtures has been probed by simulations of low-energy hydrogen bombardment of both pure carbon and boron-doped fullerene cages to observe uptake, which showed that the probability of hydrogen retention varied strongly based on impact energy [9].…”
Section: Introductionmentioning
confidence: 99%
“…This exposure was accomplished in an apparatus designed specifically for plasma treatment coupled with in situ surface analysis. 32 The main body of the chamber was constructed with stainless steel and was equipped with a load lock, specimen transfer arrangement, and hemispherical analyzer for X-ray photoelectron spectroscopy (XPS). Specimens were mounted at ground potential on a molybdenum holder using double-sided copper tape and a molybdenum clip.…”
Section: ■ Introductionmentioning
confidence: 99%